2016
DOI: 10.1111/mec.13768
|View full text |Cite
|
Sign up to set email alerts
|

ExtremeQTLmapping of germination speed inArabidopsis thaliana

Abstract: Seed germination is a key life history transition for annual plants and partly determines lifetime performance and fitness. Germination speed, the elapsed time for a nondormant seed to germinate, is a poorly understood trait important for plants' competitiveness and fitness in fluctuating environments. Germination speed varied by 30% among 18 Arabidopsis thaliana populations measured, and exhibited weak negative correlation with flowering time and seed weight, with significant genotype effect (P < 0.005). To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 95 publications
3
27
0
1
Order By: Relevance
“…A large number of AGRs were identified rapidly, and significant AGRs with a high Δ (SNP-index) were consistent with the SOC-QTL hotspots, confirming the accuracy of the QTL mapping based on the present map. In addition, we found that highly significant AGRs were subdivided into multiple QTLs (Table S6) rather than being subdivided or narrowed QTLs as previously reported34354849. These results suggested that the present high-density linkage map had sufficiently high resolution to dissect genetic variation in primary mapping populations.…”
Section: Discussionsupporting
confidence: 82%
“…A large number of AGRs were identified rapidly, and significant AGRs with a high Δ (SNP-index) were consistent with the SOC-QTL hotspots, confirming the accuracy of the QTL mapping based on the present map. In addition, we found that highly significant AGRs were subdivided into multiple QTLs (Table S6) rather than being subdivided or narrowed QTLs as previously reported34354849. These results suggested that the present high-density linkage map had sufficiently high resolution to dissect genetic variation in primary mapping populations.…”
Section: Discussionsupporting
confidence: 82%
“…A method termed as extreme QTL (X‐QTL) mapping was developed in yeast that promised a higher resolution and rapid mapping (Ehrenreich et al ., ). This has been used in mapping seed size (Guo et al ., ), germination features (Yuan et al ., ) salt tolerance (Guo et al ., ; Yuan et al ., ; Figure ) in A. thaliana . X‐QTL mapping continues to hold some promise, although it is likely to be more important for species with high recombination rates.…”
Section: Finding Associations Between Genotype and Phenotype: Linkagementioning
confidence: 99%
“… An illustrated comparison of selected linkage mapping approaches for finding associations between genotype, phenotype and environment. Stylized and re‐drawn workflow methods for (a) extreme quantitative trait loci (X‐QTL) mapping (Yuan et al ., ,), (b) genome‐wide association study (GWAS; Atwell et al ., ) and (c) nested association mapping (NAM; Buckler et al ., ), which exemplify strengths and weaknesses of these specific linkage mapping approaches. …”
Section: Finding Associations Between Genotype and Phenotype: Linkagementioning
confidence: 99%
“…For literature validation, a separate set of nine casual genes was used for each species. It 392 includes causal genes that have been cloned or indicated by joint linkage-association analysis or 393 indicated by mutant analysis (Chardon et al, 2013;Fan et al, 2016;Fukuoka et al, 2014;Gao et 394 al., 2016;Guo et al, 2015;Hu et al, 2008;Huang et al, 2012;Liu et al, 2017;Motte et al, 395 2014;Oikawa et al, 2015;Qi et al, 2008;Sharma et al, 2005;Yuan et al, 2016;Zeng et al, 396…”
Section: Arabidopsis and Rice Causal Genes Used For Training And Indementioning
confidence: 99%